Isolation and purification of a bioactive protein from indigenous basidiomycete Ganoderma australe (Fr.) Pat / Nurulaina binti Saidin - Saidin, Nurulaina (2011)
The present study attempted to purify bioactive protein from mycelia of Ganoderma culture using organic extraction method (dichloromethane and 50% ethanol) and selection of chromatographic techniques. By using crude ethanolic extract, four strains of indigenous Ganoderma australe and one from Ganoderma tsugae were assessed for their antagonistic activity against human pathogenic bacteria and yeast. All Ganoderma strains tested exhibited different levels of antibacterial activity against both Gram-positive and Gram-negative bacteria. The ethanolic extract from G. australe strain KUM60813 was selected for further protein purification on the basis of intense antibacterial activity compared to proteins from other strains tested. The protein was further isolated using ammonium sulfate precipitation and gel filtration on Sephacryl S-100 and Superdex 75 HR column. This resulted in a purification of a protein with a molecular weight of 16.6 kDa, visualized on Tricine SDS PAGE. The purified protein was assessed for its antibacterial activity using microtitre broth dilution method. The protein showed inhibitory activity towards Salmonella typhi and Escherichia coli O157:H7 with IC50 of 5.21 mg/ml and 4.04 mg/ml, respectively. It also inhibited HIV-1 reverse transcriptase with an IC50 of 1.08 mg/ml and deoxyribonuclease activity towards herring sperm DNA. The protein exhibited no antifungal activity against the plant pathogenic fungi tested and also had no ribonuclease activity. Finally, the identity of the protein was further analyzed using Mass Spectrometry and showed significant similarity to antifungal protein from Aspergillus giganteus. The study has demonstrated a simplified approach of purification of bioactive protein from mycelia of G. australe. Hence, should be adopted for convenient purification of proteins from other species of mushroom.